Peran Penalaran Hukum Dalam Proses Penemuan Hukum (Rechtsvinding) Oleh Hakim - Aemili Rara Marcia Indriastuti; Emy Handayani (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
Legal reasoning is a method of thinking using logic to seek truth or solve problems in the field of law. We are aware that the law will not always be able to keep up with the rapid pace of development. The emergence of technology has enabled various types of crimes to occur, resulting in legal vacuums. Judges, as law enforcers, need to master legal reasoning to overcome these legal vacuums through the discovery of law. There are various forms of legal reasoning, such as deductive and inductive reasoning. In addition to form, there are aspects to consider in legal reasoning, namely the ontological aspect that questions what law is, the epistemological aspect that focuses on the method of legal reasoning, and the axiological aspect that questions the purpose of legal reasoning. The discovery of law itself is divided into legal construction and legal interpretation. Ultimately, it can be concluded that legal reasoning plays a crucial role in the process of judges making legal discoveries. Legal reasoning serves as the basis, guide, guideline, and knowledge that enables judges to conduct legal discoveries genuinely based on the realization of the purpose of law itself.